Análise da distribuição espacial e dos impactos econômicos e sociais dos recursos do fundo constitucional de financiamento do Norte (FNO) para os municípios paraenses no período 1999 – 2007 - Araújo, Adriano Lima (2010)
The present work analyzes the spatial distribution of the contracted resources from FNO and the economic-social impacts generated in the cities of Pará State from 1999 until 2007, State who had presented at this period the lesser per capita GDP of the North region and one of Brazil’s lowest. In theory, the credit is the motor and dinamizer element of the growth and regional economic development and provides the growth of the productive activity and consumption of the families. After the analysis of the origin and performance of the constitutional funds, is made a comparision about the spatial distribution of the resources of that credit subsidized in the State for geographic meso-region. By the use of an econometrical approach, the final conclusions are extracted about: significant and positive statistical influence of the FNO contracts about the per capita GDP and GDP of the cities; the highest possibilities to get the FNO resources for some of the State’s meso-regions, to cities classified for PNDR typology as High Income and the cities with the average per capita GIP above average registered in the period; and, results about the impacts caused by the contracts in the variations of the per capita GDP’s and the IFDM Index of the cities.